2004
DOI: 10.1128/jb.186.7.2038-2045.2004
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-Mediated Transformation ofAspergillus awamoriin the Absence of Full-Length VirD2, VirC2, or VirE2 Leads to Insertion of Aberrant T-DNA Structures

Abstract: Reductions to 2, 5, and 42% of the wild-type transformation efficiency were found when Agrobacterium mutants carrying transposon insertions in virD2, virC2, and virE2, respectively, were used to transform Aspergillus awamori. The structures of the T-DNAs integrated into the host genome by these mutants were analyzed by Southern and sequence analyses. The T-DNAs of transformants obtained with the virE2 mutant had left-border truncations, whereas those obtained with the virD2 mutant had truncated right ends. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Involvement of VirD2 in protecting the integrity of the right border was also demonstrated in a fungal transformation system (Michielse et al, 2004); this study further showed that VirE2 similarly protects the left end of the T-DNA, while VirC2 helps ensure correct processing. Importantly, VirC2 is also required for single-copy integration in this system (Michielse et al 2004).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 81%
See 1 more Smart Citation
“…Involvement of VirD2 in protecting the integrity of the right border was also demonstrated in a fungal transformation system (Michielse et al, 2004); this study further showed that VirE2 similarly protects the left end of the T-DNA, while VirC2 helps ensure correct processing. Importantly, VirC2 is also required for single-copy integration in this system (Michielse et al 2004).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 81%
“…However, it is not clear how exactly the w domain of VirD2 is involved in T-DNA integration because the pattern of integration of the T-DNA is not affected by deletion of the ω sequence (Shurvinton et al, 1992;Tinland et al, 1995;Bravo-Angel et al, 1998;Mysore et al, 1998). Involvement of VirD2 in protecting the integrity of the right border was also demonstrated in a fungal transformation system (Michielse et al, 2004); this study further showed that VirE2 similarly protects the left end of the T-DNA, while VirC2 helps ensure correct processing. Importantly, VirC2 is also required for single-copy integration in this system (Michielse et al 2004).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 99%
“…Figure 4 shows T-DNA region integration into chromosomal DNA observed on Southern blot analysis, using genomic DNA from each stable transformant, hand, a different, 3.0-kb band was observed for transformant 23. This phenomenon has often been observed with the ATMT system (2,5,17). It was considered that integrated T-DNA suffered truncation at the corresponding restriction sites.…”
Section: Establishment Of Atmt For M Alpina 1s-4 (I)mentioning
confidence: 99%
“…In addition, Agrobacterium can transform Streptomyces, yeast, and other fungal species (Bundock et al, 1995(Bundock et al, , 2002Piers et al, 1996;de Groot et al, 1998;Abuodeh et al, 2000;Kelly and Kado, 2002;Roberts et al, 2003;Schrammeijer et al, 2003;Michielse et al, 2004), HeLa cells (Kunik et al, 2001), and sea urchin embryos (Bulgakov et al, 2006). Thus, Agrobacterium is incredibly promiscuous in its ability to mediate horizontal gene flow among numerous species of different phylogenetic kingdoms.…”
Section: Forward Genetic Screens For Plant Mutants With Altered Transmentioning
confidence: 99%